Zum Volkslied der Aromunen im Bezirk von Serres - Panopoulou, Kalliopi; Serbesis, Basilios (Zeitschrift für Balkanologie, 2014)
The Aromuns in Serres were settled in the area many years ago. They came mainly from the villages in West Macedonia and in the mountains of Pindos, bringing with them their folk culture. An important element of this culture is their folk songs, which constitute an integral part of their dancing tradition and exist in every social event of the Aromuns. There have been recorded 227 songs, most of them are in the Greek language, but there are many in the Aromun language. According to the results of the questionnaire that was distributed in 480 Aromuns of all ages we can come to the conclusion that the first generation is familiar with most of the songs, the second generation knows less and the third generation hardly knows any songs at all.